Telemedicine application based on signal processing techniques - Shaikh Salleh, Sheikh Hussain (Penerbit UTM, 2007)
It has been reported that heart diseases have been major killer all over the world in modern days. Diagnosis of these pathologies require knowledge and expensive equipments such as electrocardiogram (ECG), echocardiogram (EKG), auditory brainstem response (ABR) diagnosed machines etc. However, both resources are limited. The situation is even worst in poor and developing countries, for example there are very limited numbers of available cardiologist and equipments. One way to solve this problem is by using internet telemedicine.